Evaluating Attentional Bias in Shame Using the Dot Probe Task - (:unkn) unknown (My University, 2016)
Background: Cognitive theorists have long held that attentional biases are a central feature of psychopathology (Beck, 1976). Although shame plays a key role in psychopathology, research and theoretical models on information processing in shame is lacking. Objective: The considerable overlap both functionally and topographically between shame and negative affective states of anxiety and depression prompted our investigation in to whether there are attentional biases in shame. Method: We compared individuals with low, moderate, and high levels of shame on the dot probe task. We investigated the effect of valence and time course of such biases by exposing stimuli portraying disgust, sad, and happy faces at short (150 ms), medium (500 ms), and long (1,000 ms) durations. Results: We analyzed dot probe reaction times along three indices: conventional bias, facilitated engagement, and difficulty disengaging. Our analyses indicated order effects for the conventional bias index, in which the stimulus exposure duration impacted individuals with low amounts of shame when the questionnaires were administered first. We observed group main effects for our indices of facilitated engagement and difficulty disengaging, in which high shame individuals exhibited slowed engagement to all affective stimuli and delayed disengagement from all affective stimuli. Additional trends in the data are reported. Conclusions: Implications are discussed in terms of the perception of affect and social stimuli as threatening.
Keywords: Attention Bias; Shame